Construction of pillar[5]arene-based photochromic supramolecular polymeric system with tunable thermal bleaching rate. (28th September 2021) - Wu, Qiuxia; Zhang, Tianze; Li, Xiaoyan; Tu, Xi; Zhang, Huangcheng; Han, Jie
Abstract: Naphthopyran is targeted as the photochromic material here due to its fast photo-sensitivity, high optical density, relative chemical structural simplicity, and its colorless degradation products are also important in commercial ophthalmic applications as variable transmission lenses. In this paper, we reported the synthesis and characterization of a new class of photochromic supramolecular system containing both pillar[5]arene subunit and naphthopyran moiety in the chemical structural backbone. Owing to the supramolecular host-guest interactions of pillar[5]arene/neutral nitrile molecular recognition motif, the designed molecules could be spontaneously self-assembled. Thus, the photochromic supramolecular system indicates an efficient photochromism with convenient tunable fading rate, providing a simple and versatile strategy to fabricate photochromic supramolecular system, as well as potential applications in advanced photo-responsive materials. Graphical abstract: Image 1 Highlights: Photochromic supramolecular system was constructed via the self-assembly of the pillar [5]arene with a naphthopyran unit. The fading rate of the photochromic supramolecular system in PMMA film was faster than that in solution. An efficient strategy to tune the photochromic properties of naphthopyran was reported.